STRATEGI PUBLIC RELATIONS DALAM PENGELOLAAN MEDIA DIGITAL SEKOLAH - Zon Vanel; Lina Sinatra Wijaya; George Nicholas Huwae (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
The COVID-19 pandemic has caused schools to migrate towards digital for the delivery of information in order to support the teaching process. SMP Negeri 4 Surakarta has problems in managing digital media so the management of school information systems still overlaps in its distribution. This causes the dissemination of information to be not simultaneous and not centered on one door. The problems are often around the unclear information due to message distortion in the communication coding process which causes the message to be not well received by the audience. This study aims to design and manage a multimedia-based public relations strategy to be applied in SMP Negeri 4 Surakarta which will later be useful in managing information media used by schools. This study uses a qualitative descriptive approach with a case study model. The data was gathered through field observations, structured interviews, and documentation. The results of the study show that SMP Negeri 4 Surakarta needs a digital media management model that is more creative and interactive so that it can make it easier for teachers to transfer school knowledge and information.